EMOTIONAL EXPERIENCE OF THE EVENTS IN LIFE IN THE WRITINGS OF JOJO MOES - Esther, V. Jasuve; Solomon, P. Helmsly (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Trauma is an emotional response to a terrible event that takes place in life such as an accident, rape, or natural disaster, after the event, as shock and denial are typical afflictions in the life of an individual. There are longer-term reactions that include unpredictable emotions, flashbacks, strained relationships, and even physical symptoms like headache or nausea and other physical issues. Jojo Moyes writes confidently on the human emotions that affect them when it is experienced abruptly in life. The experiences from the traumatic expressions involve at times threat to life or the safety of a person. From the experiences, it has been identified that in any situation that leads the person’s feelings overwhelmed. The individual is also isolated in such a way that could result in trauma, sometimes involving no physical harm. There are objective circumstances that determine an event as traumatic, however, the subjective emotional experience of the event causes traumatic experience. The frightened and helpless feel have more options to have the experience of being traumatized. This article deals with the environment and how it makes the traumatic experience with negation with the writings of Jojo Moyes from the various experiences he attained through multiple approaches applied in the career of human beings.